P.027 Efficacy and Safety of Eptinezumab Initiated During a Migraine Attack: Results from the RELIEF Study. (November 2021) - Winner, PK; McAllister, P; Chakhava, G; Ailani, J; Mehta, L; Ettrup, A; Krog Josiassen, M; Lindsten, A; Bougie, JK; Cady, R
Abstract : Background: Eptinezumab is approved for migraine prevention, with demonstrated rapid onset of preventive benefit. RELIEF evaluated the efficacy and safety of eptinezumab initiated during a migraine attack. Methods: RELIEF (NCT04152083; parallel-group, double-blind, placebo-controlled) randomized adults with migraine (4-15d/mo in 3mo prior to screening) to eptinezumab 100mg or placebo, administered IV within 1-6h of qualifying migraine onset. Co-primary efficacy endpoints were time to headache pain freedom and time to absence of most bothersome symptom (MBS). Results: Eptinezumab (n=238) compared with placebo (n=242) achieved significantly faster headache pain freedom (median 4h vs 9h; hazard ratio=1.54, P =0.0006) and absence of MBS (2h vs 3h; 1.75, P <0.0001). At 2h, 23.5% and 12.0% ( P =0.0009) of eptinezumab-treated and placebo patients, respectively, reported headache pain freedom, and 55.5% and 35.8% ( P <0.0001) reported absence of MBS. Significantly fewer eptinezumab-treated patients used rescue medication within 24h (31.5% vs 59.9%; P <0.0001). Treatment-emergent adverse events occurred in 10.9% eptinezumab-treated and 10.3% placebo patients; no serious adverse events occurred. Conclusions: Infusion of the preventive migraine treatment, eptinezumab, during a migraine resulted in rapid and sustained freedom from headache pain and MBS vs placebo, starting 2h post-infusion, decreasing need for acute medication within 24h post-infusion. No notable safety findings were identified.